Making and Treating Trans Problems: The Ontological Politics of Clinical Practices - Latham, Joe (Routledge, 2017)
ABSTRACTAesthetic Plastic Surgeryproduces This essay investigates a divergence between medical and autobiographical accounts of transexuality. By analyzing a letter to the editor in the journal Aesthetic Plastic Surgery that defends trans patients as a “special case” (Selvaggi and Giordano, 2014), I examine how medicine produces trans patients as a separate category of patients. The differential treatment paths of trans and nontrans people who pursue “gender-enhancing” medical interventions demonstrate a double standard that undermines claims to act in the best interest of the patient. Using the evidence of trans men’s accounts of themselves as well as research into the experiences of trans people from across the United Kingdom, Australia, and North America, I critique the medical management of transexuality and call on clinicians to rethink the treatment practices of trans medicine.